AAV-Mediated Gene Transfer to Dorsal Root Ganglion - Yu, Hongwei (Methods Mol Biol, 2016)
Transferring genetic molecules into the peripheral sensory nervous system to manipulate nociceptive pathophysiology is a powerful approach for experimental modulation of sensory signaling and potentially for translation into therapy for chronic pain. This can be efficiently achieved by the use of recombinant adeno-associated virus (rAAV) in conjunction with nociceptor-specific regulatory transgene cassettes. Among different routes of delivery, direct injection into the dorsal root ganglia (DRGs) offers the most efficient AAV-mediated gene transfer selectively into the peripheral sensory nervous system. Here, we briefly discuss the advantages and applications of intraganglionic microinjection, and then provide a detailed approach for DRG injection, including a list of the necessary materials and description of a method for performing DRG microinjection experiments. We also discuss our experience with several adeno-associated virus (AAV) options for in vivo transgene expression in DRG neurons.